2019
DOI: 10.3390/f10090736
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Radionuclides in the Trees of Fukushima Forests 2. Study of Radiocesium Flow to Poplar Seedlings as a Model Tree

Abstract: After the nuclear power plant accident in Fukushima, radionuclides were deposited over a large area of local forest. However, almost nothing is known about radionuclide infiltration into trees. Here, we used poplar seedlings as a model to show that radiocesium can enter directly into leaves and bark, moving via ray cells through the symplastic pathways to the xylem and concentrating around the meristems, cork, and vascular cambium. During induced potassium incorporation and reduced seasonal growth, the radioce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Such a phenomenon was also related to radiocesium movement, as shown by the autoradiographies in the series of sections. This is in agreement with our finding [6], which shows that by adding 137 Cs]cesium chloride solution into poplar seedlings, 137 Cs flow could be markedly accelerated vertically through vessels, and horizontally through ray cells throughout the whole tissue if the xyloglucan content in the stem was reduced by using transgenic poplar overexpressing xyloglucanase. Although interaction might occur between radiocesium and acidic polymers in the membranes, immuno-cytochemical observation showed that the intervessel pit membranes of Acer are unlikely to contain pectic or other acidic polysaccharides [18].…”
Section: Analysis At the Cross-cut Edge Of Stemsupporting
confidence: 93%
See 1 more Smart Citation
“…Such a phenomenon was also related to radiocesium movement, as shown by the autoradiographies in the series of sections. This is in agreement with our finding [6], which shows that by adding 137 Cs]cesium chloride solution into poplar seedlings, 137 Cs flow could be markedly accelerated vertically through vessels, and horizontally through ray cells throughout the whole tissue if the xyloglucan content in the stem was reduced by using transgenic poplar overexpressing xyloglucanase. Although interaction might occur between radiocesium and acidic polymers in the membranes, immuno-cytochemical observation showed that the intervessel pit membranes of Acer are unlikely to contain pectic or other acidic polysaccharides [18].…”
Section: Analysis At the Cross-cut Edge Of Stemsupporting
confidence: 93%
“…The dispersed radiocesium landed in aerosol form on the outer surface of the bark and migrated directly into entire tree bodies through translocation to the sapwood and heartwood [4,5]. Although radiocesium is recycled among other forest components-such as living plant tissues, leaf litter, mulch, and soil-once it enters the heartwood, there is no more turnover, and it continues to accumulate [6]. This has made it very difficult to remove radiocesium from living tree plants, though we attempted to use a foliar spray of potassium solution applied by hand and by radio-controlled helicopter in a small forest, as well as the direct injection of potassium solution into tree trunks over several years in order to reduce radiocesium through the use of potassium fertilization [7], see Figure S1.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we showed that radioiodine-targeted xyloglucan was elevated in the annual rings of forest trees after a megathrust earthquake (Figure 2). Therefore, we conclude that the increased xyloglucan signals that we observed in the growth rings of forest tree trunks in the wild were likely caused, at least in part, by earthquakes, different from the intake of radionuclide in the trees due to the accident involving a nuclear power plant [1][2][3][4]. The 2011 megathrust earthquake not only triggered a nuclear power plant accident that dispersed radioiodine, which then became bound to xyloglucan in trees as an artificial event due to a human error, but also increased xyloglucan signaling in annual rings of forest trees as a plant response against seismic stress under natural phenomena.…”
Section: Discussionmentioning
confidence: 78%
“…The earthquake and tsunami on 11 March 2011 led to a meltdown followed by a hydrogen explosion at the Fukushima-Daiichi nuclear power plant in Japan, causing the dispersal of abundant radionuclides into forests and local residences by gaseous or aerosol forms [1][2][3][4]. Radioiodine and radiocesium were likely incorporated and fixed in forest trees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation